DIPLOMASI BUDAYA INDONESIA TERHADAP AMERIKA SERIKAT MELALUI MATA KULIAH GAMELAN DI UNIVERSITAS LAWRENCE - Azraa Tasya, (2022)
Adressing the issue of Indonesia's cultural diplomacy, it can be done through various ways. One of them is through traditional music such as gamelan. Gamelan has also been used as a course at several foreign universities, including under the auspices of Lawrence University in the United States of America. This research aims to discuss the forms of Indonesia's cultural diplomacy in the United States through gamelan course at Lawrence University using the concept of cultural diplomacy, the principles of cultural diplomacy, and the concept of music in International Relations. The research method that the author uses is descriptive qualitative using primary data sources and secondary data. The data collecting techniques were carried out through interviews and literature studies. Researchers conducted data analysis using qualitative data analysis techniques that linked the research questions with several theories and concepts as analytical references. The final result of this research shows that Indonesia's cultural diplomacy towards the United States through gamelan course at Lawrence University has succeeded in spreading Indonesian culture, especially gamelan, to the people of the United States through two forms of cultural diplomacy, that are education and art. Cultural diplomacy through education is carried out by the course itself which teaches how to play gamelan instruments and this course can be taken by all Lawrence University students in each semester. Meanwhile, cultural diplomacy through the arts is carried out by holding gamelan art performances every year which is played by gamelan teachers and students and can be witnessed by the general public or the entire people of United States. These activities also succeeded in creating a positive image of Indonesia among the people of the United States.